Interfaces of Complexity. Participation as Explorative Process for Organisational Development - Klaus Neundlinger; Sascha Vogel (7th International OFEL Conference on Governance, Management and Entrepreneurship: Embracing Diversity in Organisations. April 5th - 6th, 2019, Dubrovnik, Croatia, 2019)
This paper introduces the concept of "interface of complexity" as a source of creating and dealing with possible participatory approaches to organisational development. Based on an actor-network-theory approach, we conceive of interfaces as complex events, situations and transitions in a technical as well as in a non-technical sense. The latter are thought of as process or interaction interfaces between persons, departments and different echelons. Both types of interfaces cause ambiguity, conflicts or problems of translation and by that they challenge established practices, prompting novel ways of rethinking or redesigning organisational processes. We conceive of spaces of participation not so much as innovation hubs or similar structures that are deliberately founded to foster innovative approaches and solutions. Rather, they are exploration processes generated by interfaces of complexity between different actors or units. Based on the qualitative content analysis of a series of expert interviews with IT and process managers, we reconstruct the measures, taken by managers and their teams, to cope with the ambiguity and irritations originating from interfaces of complexity. By transforming those interfaces into practices that open up spaces for common exploration processes of problem solving, participatory approaches can be shown to be a major stepping stone for organisational development.
Keywords: 650; Complexity; interface; organizational culture; organisational development; particiaption